2016
DOI: 10.1007/s00203-016-1204-x
|View full text |Cite
|
Sign up to set email alerts
|

Cellulosimicrobium marinum sp. nov., an actinobacterium isolated from sea sediment

Abstract: A novel Gram stain positive actinobacterium, designated RS-7-4(T), was isolated from a sea sediment sample collected in Indonesia, and its taxonomic position was investigated using a polyphasic approach. Strain RS-7-4(T) was observed to form vegetative hyphae in the early phase of growth, but the hyphae eventually fragmented into short rods to coccoid cells. Growth occurred at 15-37 °C, pH 6.0-11.0 and in the presence of 0-7 % (w/v) NaCl. Phylogenetic analysis based on 16S rRNA gene sequence comparisons reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…Several studies have shown that actinomycetes isolated from the marine environment are metabolically active and have adapted to marine life (Bull, Stach, Ward, & Goodfellow, 2005;Lam, 2006;Valli et al, 2012). Marine actinomycetes are widely distributed in a variety of marine habitats from marine sand (Hong, Lee, Yim, Chun, & Lee, 2008), mangrove sediments (Hong et al, 2009;Hong, 2013;Azman, Othman, Velu, Cha, & Lee, 2015;Hamada et al, 2015a;Hamada et al, 2015b), seawater (Zhang, Xi, Ruan, & Huang, 2012), coastal sediments (Yu et al, 2015), and deep sea sediments (Pathom-aree et al, 2006;Bredholt et al, 2007 ;Luo et al, 2011;Zhang, Zhang, Yin, & Wang, 2015;Chen et al, 2016). The increasing number of studies on marine actinomycetes indicates that marine environment including the deep ocean, is a significant source for finding and discovering both the marine actinomycetes diversity and its secondary metabolites product.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that actinomycetes isolated from the marine environment are metabolically active and have adapted to marine life (Bull, Stach, Ward, & Goodfellow, 2005;Lam, 2006;Valli et al, 2012). Marine actinomycetes are widely distributed in a variety of marine habitats from marine sand (Hong, Lee, Yim, Chun, & Lee, 2008), mangrove sediments (Hong et al, 2009;Hong, 2013;Azman, Othman, Velu, Cha, & Lee, 2015;Hamada et al, 2015a;Hamada et al, 2015b), seawater (Zhang, Xi, Ruan, & Huang, 2012), coastal sediments (Yu et al, 2015), and deep sea sediments (Pathom-aree et al, 2006;Bredholt et al, 2007 ;Luo et al, 2011;Zhang, Zhang, Yin, & Wang, 2015;Chen et al, 2016). The increasing number of studies on marine actinomycetes indicates that marine environment including the deep ocean, is a significant source for finding and discovering both the marine actinomycetes diversity and its secondary metabolites product.…”
Section: Introductionmentioning
confidence: 99%
“…NBRC 107697 T formed a clade with G. araii NBRC 100433 T supported by high bootstrap value (Fig. 1 Amino acids and the isomers in cell-wall hydrolysates, cellwall sugars, isoprenoid quinones and the DNA G+C content were determined according to the methods described by Hamada et al [13]. Polar lipids were extracted from 100 mg freeze-dried cells, purified using the method described by Minnikin et al [23] and analysed by thin-layer chromatography using chloroform/methanol/water (65 : 25 : 4, by volume) in the first direction and chloroform/acetic acid/methanol/ water (80 : 18 : 12 : 5, by volume) in the second.…”
mentioning
confidence: 97%
“…Morphological features were observed after various periods of culture (up to seven days) under a light microscope (BX-51; Olympus) and a scanning electron microscope (JSM-6060; JEOL). Growth parameters (temperature, pH and NaCl tolerance) were determined using the methods described by Hamada et al [13]. Cell motility, anaerobic growth, Gram staining, catalase and oxidase activity were tested as described previously [14].…”
mentioning
confidence: 99%
“…Strain HIsM16-52 T was isolated from a beach sand sample collected from Ishigaki Island, Okinawa in Japan. The procedure employed for bacterial isolation was as described by Hamada et al [8]. Tryptic soy agar/broth (TSA/TSB; Difco) was used as basal medium for this study.…”
mentioning
confidence: 99%
“…The results of other physiological and biochemical analyses are summarized in the species description below. PCR amplification and 16S rRNA gene sequencing of strain HIsM16-52 T were performed as described by Hamada et al [8]. The phylogenetic neighbours were identified and pairwise 16S rRNA gene sequence similarities were calculated using the EzBioCloud [10].…”
mentioning
confidence: 99%